A new technology for cost effective low grade waste heat recovery. (September 2017) - Langan, Michael; O'Toole, Kevin
Abstract: Exergyn has developed the Exergyn Drive™, an innovative, new engine cycle which runs on hot water. This technology will enable low-grade waste heat ("LGWH") to be recovered cost effectively for the first time, with attractive returns on investment and rapid payback. LGWH is heat below 100°C and there is no cost effective solution commercially available and, as 63% of waste heat is at a temperature below 100°C, there is a significant untapped resource. Cost effectiveness is the key barriers that have left this market untapped. Exergyn's technology will change this as it is very simple, which allows costs to be reduced, and will enable LGWH to be recovered in a wide range of applications to deliver low cost, zero emission electricity on demand. The Exergyn Drive™ applies a solid state drive to utilise hot water of suitable temperatures (c. 90°C) from sources such as reciprocating engines, industrial processes or geothermal resources. Installation is also simple, potentially a flow and return from the heat source and an electrical hook up utilising heat directly from engine jackets without the need for heat exchangers, which enhances efficiency and reduces costs. The low through life costs give, making low grade waste heat recovery attractive for the first time.